PENGETAHUAN DAN MINAT MASYARAKAT PETERNAK UNTUK MENERAPKAN TEKNOLOGI INSEMINASI BUATAN - Khaifah Asgaf; Muhammad Arsan Jamili; Muhammad Rusman Rusli (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
Artificial insemination (AI) is one of the appropriate techniques in increasing cattle productivity and to improve cow genetics. However, not all people are interested in implementing IB Technology. This study aims to explain how to increase the interest of the breeder community to apply artificial insemination technology. This study uses a descriptive quantitative approach. The total sample of 33 respondents was taken by purposive sampling, namely farmers who have at least one calf produced by means of artificial insemination (IB) technology. The analysis used for knowledge and interest variables is descriptive analysis, regression analysis, and T-Test. From the research results obtained knowledge and interest are very influential in improving the application of artificial insemination (IB) technology. The contribution of increasing each variable is knowledge by 24.4% and interest by 48.8%. From these results, it can be concluded that the interest and knowledge of the farming community about artificial insemination technology is very influential or significant based on the results of the T-Test which shows that the substantial value in the attitude of farmers is (0.000) < (0.05). With the implementation of artificial insemination technology carried out by farmers, the community is expected to be able to increase the productivity and quality of their livestock genetic products Keywords: Breeding Community; Interest; Knowledge; Artificial Insemination Technology